1980
DOI: 10.1172/jci109774
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Efferent Arteriolar Vascular Tone in Regulation of Proximal Tubule Fluid Reabsorption and Glomerulotubular Balance in the Rat

Abstract: A B S T R A C T Micropunctre study was performed in 21 mildly volumne-expanded Mlunich-Wistar rats before and during partial aortic constriction to examine the effects of endogenious prostaglandins (PG) and angiotenisin II (All) on single nephron glomerular filtration rate (SNGFR) and al)solute proximal reabsorption rate (APR). Animilals received either vehicle (group 1), indomethacini (group 2), or indomethacin plus saralasin (group 3). Before aortic constriction, these inhibitors were without effect on value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
1

Year Published

1983
1983
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(50 citation statements)
references
References 43 publications
1
48
1
Order By: Relevance
“…The vasoconstrictor effect of Ang II on efferent arterioles causes changes in peritubular capillary dynamics that could increase renal tubular fluid reabsorption (33). The efferent arteriolar vasoconstriction would reduce the peritubular capillary hydrostatic pressure as well as increase peritubular capillary colloid osmotic pressure due to an increase in the filtration fraction.…”
Section: Renal Actions Of Angiotensin IImentioning
confidence: 99%
“…The vasoconstrictor effect of Ang II on efferent arterioles causes changes in peritubular capillary dynamics that could increase renal tubular fluid reabsorption (33). The efferent arteriolar vasoconstriction would reduce the peritubular capillary hydrostatic pressure as well as increase peritubular capillary colloid osmotic pressure due to an increase in the filtration fraction.…”
Section: Renal Actions Of Angiotensin IImentioning
confidence: 99%
“…In the brain, intraventricular injection of angiotensin II causes a dramatic pressor response mediated by AT 1 receptors (14). In the kidney, activation of AT 1 receptors is associated with renal vasoconstriction and antinatriuresis (15,16). Furthermore, it has been suggested that activation of AT 1 receptors at the juxtaglomerular apparatus suppresses renin release through the so-called short-loop feedback mechanism (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigators have shown under a variety of experimental conditions that changes in absolute proximal fluid reabsorption rate (APR) occur in a manner predictable from simultaneously measured levels of peritubular intracapillary oncotic and hydraulic forces (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Thus, reduction in the concentration of postglomerular plasma protein, induced by a variety of experimental maneuvers, such as intravenous infusion of large volume of colloid-free solutions, was associated with a decrease in APR (4,8).…”
Section: Introductionmentioning
confidence: 99%